Role of Subclinical Gut Inflammation in the Pathogenesis of Spondyloarthritis - Rizzo, Aroldo; Guggino, Giuliana; Ferrante, Angelo; Ciccia, Francesco (Frontiers in Medicine, 2018)
Abstract Sub-clinical gut inflammation occurring in patients affected by Spondyloarthritis (SpA) is correlated with the severity of spine inflammation. Several evidences indicate that dysbiosis occurs in SpA and that may modulate intestinal permeability and intestinal immune responses. The presence of intestinal dysbiosis is accompanied in SpA patients with the presence of zonulin-dependent alterations of gut-epithelial and gut-vascular barriers. The leakage of epithelial and endothelial surface layers is followed by the translocation of bacterial products, such as lipopolysaccharide (LPS) and intestinal fatty acid binding protein (iFABP), in the systemic circulation. These bacterial products may down-regulate the expression of CD14 on circulating monocytes leading to an “anergic” phenotype. In the gut, IL-23 may induce the expansion of innate immune cells such as mucosal associated invariant T cells (MAIT), T cells and innate lymphoid cells of group 3 (ILC3) that through the interaction with MAdCAM1 may re-circulate form the gut to the sites of SpA active inflammation. On the basis of these findings gut inflammation observed in SpA patient seems to be not only an epiphenomenon of the on going systemic inflammatory process but may represent the base camp in which inflammatory cells are activated and from whom they shuttle